Student Performance in Online Learning: E-Leadership and IT Capability Student in One of Public Universities - La Paudi, Untung; Anco, Anco (International Journal of Transdisciplinary Knowledge, 2023)
The situation in which the globe is rattled by coronavirus illness 2019 (COVID-19) has caused virtual teams to appear in all organizations and senior roles. Becomes increasingly relevant. This study time focuses on the comprehension component for improved student performance in virtual teams. Research design: quantitative and statistical data collected by online learners Study this objective to determine the influence of e-leadership on student performance and IT competency as a variable mediator using a total of 242 surveys. This sample consists of Jakarta State University students. This study's data analysis method is a structural equation model (SEM) utilizing Amos version 24. The results of this research show that e-leadership positively impacts IT capabilities. Demonstrate that e-leadership harms student performance and then that IT capability has a positive impact on student performance. There is no direct relationship between variable e-leadership and variable influence on display.